An analysis of supply response of rapeseed-mustard in different regions of Uttar Pradesh (Journal of Oilseed Brassica, 2026)
The continuing imbalance between increasing demand and slow growth in supply of oilseeds is a major concern which needs to be addressed seriously. The increase in the production of oilseed has to come through increase in acreage and /or productivity of the oilseeds. Uttar Pradesh is a very important state in the country from agricultural point of view, which occupying second position in rapeseed-mustard production. In Uttar Pradesh, an attempt was made to examine the economic factors on supply response of rapeseed mustard in different regions, and at aggregate level. The present study evaluated the impact of price and selected non-price factors on the area of rapeseed-mustard, and to analyse the short and long-run price elasticities. This macro framework study used 20 years (1989–90 to 2008–09) secondary data regarding area, productivity, farm harvest price of crops, farm harvest price of competing crops, monsoon season rainfall, percentage irrigated area of crops, and competing crop (gram). The double log Nerlovian lagged adjustment model used in present study postulates that the actual acreage under a crop in each period is adjusted in a proportion to the difference between the desired acreage in the long run equilibrium, and the actual acreage under it in the preceding year. The short-run price elasticities of acreage are directly obtained from logarithmic form of the model function. As the value of coefficient of adjustment usually lies between zero and one, the value of ‘B’ close to the unity indicates that the adjustment process is very fast. When the value of ‘B’ is close to zero, the implication is that the adjustment process is very slow to the changing prices and other non-prices factors. If the value of ‘B’ is greater than one it would mean that the farmers over adjust to the planned acreage. Speed of adjustment implies the number of years required to realize 95 per cent of the price effect which was estimated using the formula suggested by Krishna, (1992). The results showed that acreage response of rapeseed-mustard to the price of rapeseed-mustard was positive and significant in all regions of Uttar Pradesh, except Bundelkhand region. The response to the price of competing crop (gram), however, was positive and significant only in case of Central region. The lagged yield of rapeseed-mustard was found to be positive and significant only in Bundelkhand region. Rainfall had strong impact on acreage under rapeseed-mustard both at aggregate and regional levels. The percentage irrigated area showed positive and significant impact in all regions, except the Central region. The percentage irrigated area of competing crop gram was positive and significant only in the Central region, but it was negative and significant at state level. Lagged area under the concerned crop was positive and significant for Western, Central, and state as a whole. In all the cases, price as well as yield risk did not play any significant role in acreage allocation of rapeseed-mustard, except in the Central and Bundelkhand regions where the yield risk was positive and significant. The short run price elasticities varied from region to region. The impact of prices was the highest in the Western and lowest in the Central region. The comparative closeness of long run elasticity to the short run elasticity in central region revealed a greater degree of adjustment in this region. The results of speed of adjustment showed that the farmers of Central and Bundelkhand regions would take less number of years to realize 95% of price effect as compared to the farmers of other regions.